Blending Wattpad Platform and English Prose Course in Industrial Revolution Era 4.0 - Irpan Ali Rahman; Iwan Iwan (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
This paper focuses on an exploration of Wattpad platforms and English prose course as blended learning models in undergraduate students. In the era of industrial revolution 4.0, the use of blended learning models is an alternative solution to the challenges of the times in integrating technological progress with learning. This study used descriptive qualitative research method to examine the concept of blending of wattpad platforms and English prose course. This research finding showed that wattpad platforms as a digital media resources contain intellectual property in the form of prose literary works with various genres. It is very interesting to be used as English teaching material. Wattpad offers easy access to English prose material so that it is more flexible to maximize the time and place of the English learning process. English prose that contains language content such as vocabulary, phrases, sentences, and dialogues which become the media of the writer to express his ideas to his readers. The use of wattpad platforms media helps students as literary readers in transferring the contents of literary works to their readers to obtain a more meaningful learning process because it is rich in moral and social values. In addition, wattpad platforms offer opportunities to respond and appreciate literary work through the reader response features provided by wattpad. Through blended learning design, English learning process can be done either face-to-face or online between lecturers and students to provide maximum learning outcomes. In the end, the learning design of the blending wattpad platforms with the English prose course is expected to be implemented as an alternative in learning English processes for advanced learners.